Cognition from on high and down low verticality and construal level. [article]. - Slepian, Michael L.; Masicampo, E.J.; Ambady, Nalini
Across 7 studies, the authors examined the relationship between experiences of verticality and abstract versus concrete processing. Experiencing high, relative to low, verticality led to higher level identifications for actions (Study 1), greater willingness to delay short-term monetary gains for larger long-term monetary gains (Study 2 and 5), and more frequent perceptions for meaningful relationships between objects and categories (Studies 3, 4, and 6), demonstrating that high verticality leads to more high level construals. Mechanisms of these effects were exploded, and the studies present evidence suggesting that mood (Studies 3 and 4), felt power (Study 4), arousal (Study 4) perceptual scope (Study 4), superficial semantic associations (Study 5), and movement (Study 5) do not mediate these effects. Instead, we found that minimal experiences of verticality influence construal level (Study 6) and that verticality can influence construal level independent to the many plausible mediators. Furthermore, the relationship is reciprocal with abstract and concrete processing influence the verticality of one?s visual perspective (Study 7), suggesting an intimate link between construal level (abstract vs. concrete processing) and experiences of verticality. - - (from the authors)
Keywords: Construal level-Periodicals.; Cognitive processing-Periodicals.; Verticality-Periodicals.; Metaphor-Periodicals.